Secondary Psychosis Following Neoadjuvant AC-T Chemotherapy for Triple-Negative Breast Cancer: Case Report and Literature Review of Psychosis Postchemotherapy - Alshehri, Sultan; Assiri, Hatem; Alsalem, Moayyad; Alharbi, Majed A. (Case Reports in Psychiatry, 2022)
Triple-negative breast cancer is a unique subtype among breast cancers. Management includes a neoadjuvant chemotherapy regimen. Psychiatric complications of the regimen have not been reported before. We present a case of acute psychosis after the second cycle of chemotherapy in a 42-year-old woman with triple-negative breast cancer. The patient presented with sudden irritability, agitation, disorganization in speech and behavior, and paranoia involving her coworkers conspiring against her and causing her trouble with the law for 4 days. She was in her usual state of health until after her second cycle of chemotherapy. This was the first presentation of psychotic symptoms in her life. She was conscious and oriented. There were no neurologic deficits. She denied any change in her mood and any features of hallucinations. She was uncooperative, restless, had flight of ideas, and persecutory delusions. The remainder of the examination was normal. An autoimmune process, nervous system infection, or psychosis secondary to the chemotherapy were suspected. Serum electrolytes and other biochemical parameters were normal. Imaging of the brain showed no signs of acute brain insults or intracranial metastasis. Cerebrospinal fluid analysis and culture showed no abnormality or growth. The work-up revealed that neurologic, infectious, or autoimmune causes of her psychotic symptoms were less likely. Thus, a diagnosis of psychosis secondary to chemotherapy was considered. Treatment was with paliperidone, risperidone, clonazepam, and sertraline. Over the course of treatment, she showed substantial improvement and completed all of the chemotherapy sessions without adverse effects. In summary, we report a case of a patient whose initial chemotherapy course was complicated by psychosis. Since the neurotoxic and psychiatric effects of chemotherapeutics are not yet sufficiently elucidated, our case emphasizes that early signs of behavioral changes in patients receiving chemotherapy should trigger comprehensive psychiatric evaluation and monitoring of the patient’s mental state.